LEGAL POLITICS OF CRIMINALIZATION AND DECRIMINALIZATION OF CRIMINAL ACTS OF CORRUPTION: A COMPARISON OF THE RULES OF PRABOWO, JOKOWI, AND SBY - Dharma, Satria Nashuha; Nugroho, Hibnu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRACTCorruption in Indonesia is an extraordinary crime with systemic impacts on governance and public welfare. This normative legal study analyzes the differences in focus and legislative frameworks of anti-corruption policy across the administrations of Presidents Joko Widodo and Prabowo Subianto. Under President Joko Widodo, anti-corruption efforts faced significant setbacks. The 2019 revision of Law No. 19 on the KPK was widely criticized for weakening the institution's independence. Further legislation, including the Omnibus Law on Job Creation and the 2023 Criminal Code (KUHP), introduced new corruption risks and created legal disharmony. These developments contributed to a decline in Indonesia's Corruption Perceptions Index (CPI), marking the Jokowi era with institutional weakening and controversial reforms. In contrast, the Prabowo Subianto administration presents an evolving orientation. Early policy narratives prioritize asset recovery through restorative justice and strengthening the roles of the Attorney General’s Office and the Police. However, concrete legislative reforms remain limited. While this approach suggests a potential for stronger deterrence, it also raises concerns that political compromise could lead to implicit decriminalization. Overall, Indonesia’s anti-corruption legal politics reflect a complex dynamic shaped by fluctuating political will and competing interests. The Jokowi era was defined by institutional erosion, while the Prabowo era confronts the dilemma of balancing asset recovery, institutional strengthening, and political stability. The study concludes that the effectiveness of future anti-corruption efforts will depend on consistent political will to establish strong, transparent, and public-oriented regulations.Keyword: Corruption, Legal Politics, Criminalization and Decriminalization, Corruption Eradication Commission (KPK), Anti-Corruption LegislationABSTRAKKorupsi di Indonesia digolongkan sebagai kejahatan luar biasa yang berdampak sistemik pada tata kelola pemerintahan dan kesejahteraan publik. Studi hukum normatif ini menganalisis perbedaan fokus dan kerangka legislatif antikorupsi antara masa pemerintahan Presiden Joko Widodo dan Presiden Prabowo Subianto. Di bawah Joko Widodo, upaya antikorupsi mengalami pelemahan signifikan. Revisi UU KPK No. 19 Tahun 2019 dikritik karena melemahkan independensi institusi. Selain itu, legislasi seperti Omnibus Law Cipta Kerja dan KUHP 2023 dianggap menciptakan risiko korupsi baru dan ketidakharmonisan hukum. Perkembangan ini berkontribusi pada penurunan Indeks Persepsi Korupsi (CPI) Indonesia. Era Jokowi ditandai oleh pelemahan institusional dan reformasi yang kontroversial. Sebaliknya, administrasi Prabowo Subianto menampilkan orientasi yang berbeda. Narasi kebijakan awal menitikberatkan pada pemulihan aset melalui keadilan restoratif serta penguatan Kejaksaan Agung dan Kepolisian. Meskipun reformasi legislatif konkret masih terbatas, pendekatan ini menyiratkan potensi deterensi yang lebih kuat. Namun, hal ini juga menimbulkan kekhawatiran bahwa kompromi politik dapat mengarah pada dekriminalisasi implisit. Secara keseluruhan, politik hukum antikorupsi Indonesia mencerminkan dinamika yang kompleks, dibentuk oleh kemauan politik yang tidak stabil. Era Jokowi diwarnai erosi institusional, sementara era Prabowo menghadapi dilema untuk menyeimbangkan pemulihan aset, penguatan kelembagaan, dan stabilitas politik. Efektivitas upaya antikorupsi di masa depan sangat bergantung pada konsistensi kemauan politik untuk menciptakan regulasi yang kuat, transparan, dan berorientasi publik.Kata Kunci: Korupsi, Politik Hukum, Kriminalisasi dan Dekriminalisasi, Komisi Pemberantasan Korupsi (KPK), Legislasi Antikorupsi.